Angioedema in chronic spontaneous urticaria is underdiagnosed and has a substantial impact: Analyses from ASSURE‐CSU. Issue 8 (15th July 2018) - Sussman, G.; Abuzakouk, M.; Bérard, F.; Canonica, W.; Oude Elberink, H.; Giménez‐Arnau, A.; Grattan, C.; Hollis, K.; Hunter, S.; Knulst, A.; Lacour, J.‐P.; Lynde, C.; et al.
Abstract: Background: ASSURE‐CSU revealed differences in physician and patient reporting of angioedema. This post hoc analysis was conducted to evaluate the actual rate of angioedema in the study population and explore differences between patients with and without angioedema. Methods: This international observational study assessed 673 patients with inadequately controlled chronic spontaneous urticaria (CSU). Physicians abstracted angioedema data from medical records, which were compared with patient‐reported data. Patients in the Yes‐angioedema category had angioedema reported in the medical record and a patient‐reported source. For those in the No‐angioedema category, angioedema was reported in neither the medical record nor a patient‐reported source. Those in the Misaligned category had angioedema reported in only one source. Statistical comparisons between Yes‐angioedema and No‐angioedema categories were conducted for measures of CSU activity, health‐related quality of life (HRQoL), productivity and healthcare resource utilization (HCRU). Regression analyses explored the relationship between Dermatology Life Quality Index (DLQI) score and angioedema, adjusting for important covariates. Results: Among evaluable patients, 259 (40.3%), 173 (26.9%) and 211 (32.8%) were in the Yes‐angioedema, No‐angioedema and Misaligned category, respectively. CSU activity and impact on HRQoL, productivity, and HCRU was greater for Yes‐angioedema patients than No‐angioedema patients. After covariate adjustment, mean DLQI score was significantly higher (indicating worse HRQoL) for patients with angioedema versus no angioedema (9.88 vs 7.27, P < .001). The Misaligned category had similar results with Yes‐angioedema on all outcomes. Conclusions: Angioedema in CSU seems to be under‐reported but has significant negative impacts on HRQoL, daily activities, HCRU and work compared with no angioedema. Abstract : (A) Initial frequency: Angioedema in the past 12 months was more frequently reported by CSU patients who completed the survey (65.8%) than recorded in the medical record (41.0%).(B) Revised frequency: Among all CSU patients, only 26.9% had no angioedema episodes at all. Of the 32.8% of patients with misaligned reporting of angioedema in the past 12 months, 97.2% reported having had angioedema, but it was not noted in the medical record.(C) Regression analysis: CSU patients with angioedema have significantly lower HRQoL than patients without angioedema*: least‐squares mean DLQI total scores by angioedema category. *LS means are from an analysis of covariance model with covariates: angioedema classification, UAS7TD score (continuous), age at enrolment (continuous), sex (male and female), country (Canada, France, Germany, Italy, Spain, the Netherlands and the United Kingdom), disease duration from diagnosis to enrolment (continuous) and comorbidities at enrolment (hypersensitivity to NSAIDs [yes/no], Hashimoto's [yes/no] and asthma [yes/no]). DLQI, Dermatology Life Quality Index; HRQoL, health‐related quality of life; NSAID, nonsteroidal anti‐inflammatory drug; SE, standard error; UAS7TD = Urticaria Activity Score over 7 Days, twice‐daily assessment.